The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1007/bf00443236
|View full text |Cite
|
Sign up to set email alerts
|

Cellular glycogen, ?-1,2-glucan, poly-?-hydroxybutyric acid and extracellular polysaccharides in fast-growing species of Rhizobium

Abstract: Synthesis of acidic exopolysaccharides, neutral cellular polysaccharides and poly-beta-hydroxybutyric acid (PHB) by Rhizobium is strongly dependent on cultural conditions and the strains used. Exopolysaccharide production by R. leguminosarum, R. Phaseoli and R. trifolii closely parallels growth, whereas R. meliloti mainly excretes (low mol wt) polysaccharides when cell propagation is limited by lack of a necessary growth element (nitrogen) and an excess of carbon source is still present in the medium. In all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
0
6

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 21 publications
5
53
0
6
Order By: Relevance
“…Synthesis of PHB is dependent on growth conditions and strain of rhizobia. Evidence suggests that accumulation of PHB granules is initiated by growth-limiting conditions as a reserve source of carbon (Zevenhuizen, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of PHB is dependent on growth conditions and strain of rhizobia. Evidence suggests that accumulation of PHB granules is initiated by growth-limiting conditions as a reserve source of carbon (Zevenhuizen, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The first group, accumulate PHB during the stationary phase requires an excess of the carbon sources .The second group accumulate PHB during the log phase (Bormann et al, 1998).Regarding of glycogen (Preiss, 1984) emphasized that glycogen is existing in enteric genera, including Enterobacter under conditions of stresses associated with infection and environmental survival. (Zevenhuizen, 1981) said that under growth-limiting conditions, free-living rhizobial cells produce glycogen simultaneously with PHB. This suggests that glycogen metabolism may fulfil a similar role to PHB (Dunn et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of cellular glycogen and PHB is initiated only under growth-limiting conditions such as saline soil. When the external carbon source is exhausted, glycogen and PHB are metabolized by the cells, sustaining their longevity and thus act as true reserve materials (Zevenhuizen, 1981). Ceyhan and Ozdemir , (2011) isolated the Enterobacter aerogenens strain 12Bi, and they reported that it was excellent PHB granules producer, as its main carbon storage compound and it was found that PHB production beginning from 16.66 (%).…”
Section: Introductionmentioning
confidence: 99%
“…S. meliloti can also accumulate intracellular carbon polymers such as glycogen and polyhydroxybutyrate (PHB), notably under growth-limiting conditions (8). PHB appears to be critical for N 2 fixation in young developing M. sativa nodules, and glycogen synthesis is essential for N 2 fixation in mature M. sativa nodules (9).…”
mentioning
confidence: 99%
“…PHB appears to be critical for N 2 fixation in young developing M. sativa nodules, and glycogen synthesis is essential for N 2 fixation in mature M. sativa nodules (9). In free-living S. meliloti cells, PHB accumulates when C availability exceeds that of other major nutrients such as N (i.e., at a C/N molar ratio greater than 10) (8) and/or when the cells have excess reducing capacity and need to regenerate NAD(P)H (10). Thus, PHB is a storage compound for both C and reducing power that also confers long-term persistence under starvation conditions (11).…”
mentioning
confidence: 99%